2021
DOI: 10.3389/fonc.2021.713853
|View full text |Cite
|
Sign up to set email alerts
|

Immune Checkpoints OX40 and OX40L in Small-Cell Lung Cancer: Predict Prognosis and Modulate Immune Microenvironment

Abstract: BackgroundOX40 and OX40 ligand (OX40L), as essential immune checkpoint (IC) modulators, are highly correlated with cancer immunity regulation as well as tumor microenvironment (TME). Immunotherapy showed outstanding advantages in small-cell lung cancer (SCLC) therapy. However, functions and clinical significance of OX40 and OX40L in SCLC were not clear yet.Materials and MethodsSCLC samples of 143 patients were collected for immunohistochemistry (IHC) or whole-exome sequencing (WES). We comprehensively explored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 56 publications
0
4
1
Order By: Relevance
“…[ 68 ] Studies in SCLC, melanoma, and pancreatic ductal adenocarcinoma have yielded similar results. [ 69 , 70 ] Our study did not show any significant survival benefit concerning OX40L expression, which might partly be explained by the low number of included cases. However, we found that AC TCs typically expressed OX40L at lower levels than other LNEN TCs.…”
Section: Discussioncontrasting
confidence: 57%
“…[ 68 ] Studies in SCLC, melanoma, and pancreatic ductal adenocarcinoma have yielded similar results. [ 69 , 70 ] Our study did not show any significant survival benefit concerning OX40L expression, which might partly be explained by the low number of included cases. However, we found that AC TCs typically expressed OX40L at lower levels than other LNEN TCs.…”
Section: Discussioncontrasting
confidence: 57%
“… 207 Mouse models have shown that specific antibodies that stimulate OX40 can reduce the number of Tregs, thereby maintaining the function of effector T cells and showing high antitumor activity. 208 210 …”
Section: Immune Stimulatory Molecules On T Cellsmentioning
confidence: 99%
“…The absence of functional and cell type-specific methylation analyses in our study does not allow us to conclude causal methylation repatterning of immune checkpoint genes due to BAP1 aberrancy in uveal melanoma. However, there is emerging evidence pointing towards an expression of immune cell-specific immune checkpoint genes, for example, GITR, OX40, 4-1BB, CD27, and CD40, in tumor cells [24][25][26][27][28]. Yan et al could prove that melanoma cell-intrinsic CD40 plays an important role in the inhibition of tumor growth and is able to induce malignant cell death [29].…”
Section: Discussionmentioning
confidence: 99%